The analysis of financial performance: the case study for Amanah Raya Trustee (ART): factors that contribute to the difference in net asset value between public unit trust and trustee holders - Mazlan, Muhammad Akmal (2010)
This study reveals on the important, roles and responsibilities of a Trustee company to all Unit Trust Funds. Towards that, Trustee companies such as ART must follow the rules and guidelines by Securities Commission. Furthermore, trustee companies did not evaluate the performance of the company based on it’s financial statement which is prepared yearly or quarter of a year. Trustee companies will evaluate the performance of a company everyday. To analyze the company that involve in this study, I will use the data from Unit Trust Fund and data prepared by ART. From that, I will identify the factors that contribute to the difference in Notification of Difference between Unit Trust Fund and Trustee companies. An analysis and valuation need to do everyday. It includes the calculation of dividend, interest charges, custody, foreign exchange and settlement in each transaction. This all are needed to justify and proof to my case study in finding the factors that make the difference in Notification of Difference in Net Asset Value between Management Companies and Trustee companies.